The Long Pentraxin PTX3 as a New Biomarker and Pharmacological Target in Age-Related Macular Degeneration and Diabetic Retinopathy - Stravalaci, Matteo; Ferrara, Mariantonia; Pathak, Varun; Davi, Francesca; Bottazzi, Barbara; Mantovani, Alberto; Medina, Reinhold J.; Romano, Mario R.; Inforzato, Antonio (Frontiers in Pharmacology, 2022)
Age related macular degeneration (AMD) and diabetic retinopathy (DR) are multifactorial, neurodegenerative and inflammatory diseases of the eye primarily involving cellular and molecular components of the outer and inner blood-retina barriers (BRB), respectively. Largely contributed by genetic factors, particularly polymorphisms in complement genes, AMD is a paradigm of retinal immune dysregulation. DR, a major complication of diabetes mellitus, typically presents with increased vascular permeability and occlusion of the retinal vasculature that leads, in the proliferative form of the disease, to neovascularization, a pathogenic trait shared with advanced AMD. In spite of distinct etiology and clinical manifestations, both pathologies share common drivers, such as chronic inflammation, either of immune (in AMD) or metabolic (in DR) origin, which initiates and propagates degeneration of the neural retina, yet the underlying mechanisms are still unclear. As a soluble pattern recognition molecule with complement regulatory functions and a marker of vascular damage, long pentraxin 3 (PTX3) is emerging as a novel player in ocular homeostasis and a potential pharmacological target in neurodegenerative disorders of the retina. Physiologically present in the human eye and induced in inflammatory conditions, this protein is strategically positioned at the BRB interface, where it acts as a “molecular trap” for complement, and modulates inflammation both in homeostatic and pathological conditions. Here, we discuss current viewpoints on PTX3 and retinal diseases, with a focus on AMD and DR, the roles therein proposed for this pentraxin, and their implications for the development of new therapeutic strategies.